THE INFLUENCE OF CONTENT MARKETING, CELEBRITY ENDORSEMENT, ONLINE CUSTOMER REVIEW, AND PRICE CONSCIOUSNESS ON PURCHASE INTENTION OF SOMETHINC SERUM PRODUCTS IN DKI JAKARTA PROVINCE - Yennida Parmariza; Dony Ary Nugroho; Engga Probi Endri (Bajang Institute, 2026)
This research aims to analyze the Influence of Content Marketing, Celebrity Endorsement, Online Customer Review and Price Consciousness on Purchase Intention of Somethinc Serum Products in DKI Jakarta Province, the sample to be used is between 100-150 people of DKI Jakarta province aged 17-45 years who have purchase intention of Somethinc Serum products. The data collection method uses a survey method using a questionnaire research instrument, while the sampling method uses a non-probability sampling method with a convenience sampling technique. The results of this study prove that Content Marketing does not have a significant effect on purchase intention of Somethinc Serum in DKI Jakarta province, Celebrity Endorsement does not have a significant effect on purchase intention of Somethinc Serum in DKI Jakarta province while Online Customer Review and Price Consciousness have an effect on purchase intention of Somethinc Serum in DKI Jakarta province.